Development of Control Strategies and Implementation to Electrical Water Heaters for Energy Conservation - FEYZİOĞLU, AHMET (INST INFORMATION & COMMUNICATION TECHNOLOGIES-BULGARIAN ACAD SCIENCES, 2016)
Optimum design for storage type Electric Water Heaters (EWHs) was analyzed for energy conservation and maximum hot water output. Single and dual tank EWHs were compared with each other. For each comparison, data were gathered for tank volumes and power ratings ranging 100-400 l and 1-4 kW respectively. Different dual tank EWHs were designed with different control mechanisms to find which one had the optimum outcome. For these comparisons, dual tank EWHs in which the upper part of the tanks had 25% of the total volume and 75% of the total power rating were used. A five day usage period of an EWH in a typical household was simulated on SIMULINK. To minimize this energy loss, transient analysis on FLUENT was performed to see how long it took for the outlet water temperature. In these simulations, single and dual tank EWHs with different control mechanisms were compared with each other to find the design with minimum energy consumption and maximum hot water output. From these results the most efficient control system cost analysis was determined for minimum operating cost and minimum carbon footprint through optimized control strategies.
Keywords: Control; energy efficiency; optimization; steady-state heat transfer; water heaters